Fenomena Harmful Algal Blooms (HABs) di Pantai Ringgung Teluk Lampung, Pengaruhnya dengan Tingkat Kematian Ikan yang Dibudidayakan pada Karamba Jaring Apung - Ade Irawan; Qadar Hasani; Herman Yuliyanto (Jurnal Penelitian Pertanian Terapan, 2015)
Fish mortality in the Bay of Lampung not only wild fish, but also fish farmed in cages, especially Ringgung Beach. One which caused by harmful algal abundance that occur was increased input contaminants by both natural and anthropogenic sources. This study aims to analyze the influence of harmful algal blooms (HABs) the amount and frequency of fish mortality in cage Ringgung Lampung Bay. The study was conducted at three research stations based KJA density. The results of the study found 33 species of phytoplankton, 14 species have potential as HABs can cause the death of fish. The highest abundance was kind Cochlodinium that reach 63.738 cells/liter. Phytoplankton diversity index value with the lowest value occurred at station 3 on June 19, 2013 ie the date of 0705. The highest phytoplankton diversity values occurred at Station 2 on June 12, 2013 is 2,451. Uniformity values of phytoplankton in the waters of Beach Ringgung obtained in the high category with a value above 0.5 or close to 1, which indicates that the spread of the individual any kind of relatively evenly. Except at station 3 which has a relatively low value (0.228 on June 19, 2013, 0291 on June 26, 2013, and 0446 on July 3, 2013). Effect of HABs on the fishing mortality rate is indicated by regression analysis. Correlation coefficient at station 1 shows the value of 0.5208. While on station 2 shows 0.6937. Harmful algal blooms shown to affect mortality rates of fish in floating net Ringgung Beach. They have triggered reduced oxygen levels in the water that could potentially cause the death of wild fish and farmed in floating net Keywords: Dead fish, harmful phytoplankton, floating net